THE INFLUENCE OF E-CATALOG EFFECTIVENESS, TENDER INFORMATION, AND PRICE DETERMINATION ON CONSTRUCTION PROCUREMENT SERVICES IN THE CITY OF TANGERANG - Cucu Sudrajat; Esaka Pratala; Yudi Nur Supriyadi; Asep Sugara (Gapenas Publisher, 2026)
This study examines a public administration issue concerning the effectiveness of the e-catalog system, tender information, and price determination in improving construction procurement services in Tangerang. The research aims to analyze the influence of e-catalog effectiveness, tender information, and price determination on construction procurement services. A quantitative approach was employed involving construction service providers in Tangerang using a saturated sampling technique. The collected data were analyzed using multiple regression analysis and the coefficient of determination to test the proposed hypotheses. The findings reveal that e-catalog effectiveness does not have a significant effect on construction procurement services, whereas tender information and price determination demonstrate significant positive effects. Simultaneously, all independent variables significantly influence construction procurement services. However, effective implementation depends not only on statistical significance but also on technical readiness, adaptive regulatory support, and adequate dissemination among construction service providers.